Relationship between plasma aldosterone levels and arterial stiffness parameters in hypertensive patients with subclinical vascular damage - L. Petramala; A. Concistrè; M. Mezzadri; F. Sarlo; F. Circosta; M. Schina; M. Soldini; G. Iannucci; C. Letizia (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2022)
Purpose: Aldosterone plays important role in cardiovascular damage. Aim was to evaluate arterial subclinical damage through arterial stiffness parameters in patients with Essential Hypertension (EH) and Primary Aldosteronism (PA). Methods: From 2018 to 2019 we consecutively enrolled 82 subjects (37 males and 45 women), distinguished in two groups: 60 EH [systolic blood pressure (SBP) 143.4 ± 16.7 mmHg, diastolic blood pressure (DBP) 89.5 ± 12.1 mmHg] and 22 PA (SBP 149 ± 19.5 mmHg, DBP 92.7 ± 12.4 mmHg) [5 with aldosterone-secreting adrenal adenoma(APA), 17 with idiopathic aldosteronism(IHA)]; 40 matched normotensive subjects (NS) were enrolled (SBP 109.7 ± 6.2 mmHg, DBP 71.3 ± 9.7 mmHg). We used non-invasive applanation tonometer to acquire pressure waveform. Results: PA patients showed higher μ-Albuminuria (UAE) (65.7 ± 11.0mg/24 h) than EH and NS (21.5 ± 7.0 mg/24 h and 21.5 ± 7.0 mg/24 h, respectively); APA group showed increased levels of arterial stiffness index (11.7 ± 4.8 m/s; p < 0.02) compared to EH subjects (8.3 ± 3 m/s) and NS subjects (7.2 ± 1.7 m/s) as well as higher carotid intima-media thickness (c-IMT); APA patients showed significant reduction of subendocardial viability ratio (SEVR) and travel time of the reflected waves (TI) respect EH and NS. PA groups showed high percentage of augmented “worsening age” (60%), compared to EH (38%) and NS (37%). PAC was positively correlated with Arterial Stiffness Index. Performing multiple linear regression analysis (evaluating anthropometric and biochemical parameters), we found UAE as predictor of Augmentation Index, Arterial Stiffness Index and Travel Time of reflected waves in the enrolled population. Conclusion: PA patients showed higher cardiovascular subclinical damage respect to EH; UAE excretion had significant correlation with aldosterone, resulting best marker of subclinical vascular remodeling.